Physical fitness is a major determinant of femoral neck and lumbar spine bone mineral density. - Pocock, N A (1986)
The relationship between physical fitness and bone mass in the femoral neck, lumbar spine, and forearm was studied in 84 normal women. Femoral neck and lumbar spine bone mineral density and forearm bone mineral content were estimated by absorptiometry. Fitness was quantitated from predicted maximal oxygen uptake. Femoral neck and lumbar bone mineral density were significantly correlated with fitness as well as age and weight. In the 46 postmenopausal subjects, fitness was the only significant predictor of femoral neck bone mineral density, and both weight and fitness predicted the lumbar bone mineral density. These data represent the first demonstration of a correlation between physical fitness, and, by implication, habitual physical activity, and bone mass in the femoral neck; they also support the previous reported correlation between lumbar bone mass and physical activity. The data suggest that increased physical fitness may increase bone mass at the sites of clinically important fractures in osteoporosis.